How Soviet Legacies Shape Russia’s Response to the Pandemic: Ethical Consequences of a Culture of Non-Disclosure - Shok, Nataliya (Kennedy Institute of Ethics journal, 2020)
, ABSTRACT:, The COVID-19 pandemic required strong state responsibility for the health of its citizens and the effective allocation of healthcare resources. In Russia, extreme circumstances reveal hidden Soviet patterns of public health. This article illuminates how Russia has implemented some changes within its health insurance structures but also has maintained the paternalistic style of state governing within public health practices. The authors examine key neo-Soviet trends in Russian society revealed during the pandemic: the ethics of silence, a culture of non-disclosure, and doublethinking. Additionally, we argue that both modern Russian medicine and healthcare demonstrate gaps in implementing robust bioethical frameworks compared with the United States. Using a robust analysis of healthcare and state practice during the COVID-19 pandemic within the framework of global bioethics, this article aims to respond to Russian history and culture in order to advance the development of bioethics.